Peaches for Monsieur le Curé - Harris, Joanne, 1964- (Penguin Books, 2013)
"When Vianne Rocher receives a letter from beyond the grave, she has no choice but to return to Lansquenet, where she once owned a chocolate shop and learned the meaning of home. But returning to one's past can be a dangerous pursuit, and Vianne and her daughters find the beautiful French village changed in unexpected ways: women veiled in black, the scent of spices in the air, and facing the church, a minaret. Most surprising of all, her old nemesis, Francis Reynaud, desperately needs her help. Can Vianne work her magic once again?"-- Page 4 of cover.